2019
DOI: 10.1007/s00415-019-09307-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel COL6A2 mutation causing late-onset limb-girdle muscular dystrophy

Abstract: Limb-girdle muscular dystrophies (LGMD) are genetic disorders characterized by weakness of predominantly proximal limb and trunk muscles due to progressive loss of muscle tissue. Collagen VI-related muscular dystrophies usually display more generalized muscle involvement combined with contractures and/or hyperlaxity of distal finger joints. LGMD-like phenotype of collagenopathy has only rarely been described and as reported is usually of childhood onset. We identified a Finnish family with COL6A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…MD is an autosomal dominant inheritance disease that typically manifests in adulthood 6 . Our patient, a 32-year-old individual, has been experiencing symptoms of MD for the past 12 years.…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD is an autosomal dominant inheritance disease that typically manifests in adulthood 6 . Our patient, a 32-year-old individual, has been experiencing symptoms of MD for the past 12 years.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…A significant number of cases of idiopathic azoospermia may have a genetic etiology. Consequently, some of these patients may harbor larger trinucleotide repeat alleles, which can contribute to an elevated risk of heritable diseases in their progeny 6 , 7 , 14 , 15 .…”
Section: Clinical Discussionmentioning
confidence: 99%
“…In 2018, the classification of LGMDs was refined [ 100 ]. The refined classification of LGMDs, including the names of genes and proteins of LGMD-causing genetic variants, is presented in Table 1 [ 100 , 101 , 102 , 103 ]. Several LGMDs are not listed in the refined classification because they were found to be associated with other diseases, discovered in only one family and not in any patients subsequently diagnosed, or simply misreported.…”
Section: Trim32 and Limb–girdle Muscular Dystrophies (Lgmds)mentioning
confidence: 99%
“…Many genes are associated with a broad range of phenotypes, and these ranges are continuously expanding. [115][116][117] Proximal weakness in particular occurs not only in LGMD, but also in many other inherited myopathies (eg, Bethlem myopathy, [118][119][120][121][122] congenital myopathies, 7,121,122 myofibrillar myopathies, 121 and others). Indeed, WES has revealed that these disorders account for a significant proportion of patients with LGMD-like phenotypes.…”
Section: General Approachmentioning
confidence: 99%